The IL-1/IL-1 receptor axis and tumor cell released inflammasome adaptor ASC are key regulators of TSLP secretion by cancer associated fibroblasts in pancreatic cancer. Issue 1 (13th February 2019) - Brunetto, Emanuela; De Monte, Lucia; Balzano, Gianpaolo; Camisa, Barbara; Laino, Vincenzo; Riba, Michela; Heltai, Silvia; Bianchi, Marco; Bordignon, Claudio; Falconi, Massimo; Bondanza, Attilio; Doglioni, Claudio; et al.
Abstract : Background: The thymic stromal lymphopoietin (TSLP), a key cytokine for development of Th2 immunity, is produced by cancer associated fibroblasts (CAFs) in pancreatic cancer where predominant tumor infiltrating Th2 over Th1 cells correlates with reduced patients' survival. Which cells and molecules are mostly relevant in driving TSLP secretion by CAFs in pancreatic cancer is not defined. Methods: We performed in vitro, in vivo and ex-vivo analyses. For in vitro studies we used pancreatic cancer cell lines, primary CAFs cultures, and THP1 cells. TSLP secretion by CAFs was used as a read-out system to identify in vitro relevant tumor-derived inflammatory cytokines and molecules. For in vivo studies human pancreatic cancer cells and CAFs were orthotopically injected in immunodeficient mice. For ex-vivo studies immunohistochemistry was performed to detect ASC (apoptosis-associated speck-like protein containing a caspase recruitment domain) expression in surgical samples. Bioinformatics was applied to interrogate published data sets. Results: We show in vitro that IL-1α and IL-1β released by pancreatic cancer cells and tumor cell-conditioned macrophages are crucial for TSLP secretion by CAFs. Treatment of immunodeficient mice orthotopically injected with human IL-1 positive pancreatic cancer cells plus CAFs using the IL-1R antagonist anakinra significantly reduced TSLP expression in the tumor. Importantly, we found that pancreatic cancer cells release alarmins, among which ASC, able to induce IL-1β secretion in macrophages. The relevance of ASC was confirmed ex-vivo by its expression in both tumor cells and tumor associated macrophages in pancreatic cancer surgical samples and survival data analyses showing statistically significant inverse correlation between ASC expression and survival in pancreatic cancer patients. Conclusions: Our findings indicate that tumor released IL-1α and IL-1β and ASC are key regulators of TSLP secretion by CAFs and their targeting should ultimately dampen Th2 inflammation and improve overall survival in pancreatic cancer.